Analysis of air temperature and relative humidity: study of microclimates - Alves, Elis Dener Lima (2012)
Understanding the variability of climate elements in time and space is fundamental to the knowledge of the dynamics of microclimate. Thus, the objective was to analyze the variability of air temperature and relative humidity on the Cuiabá campus of the Federal University of Mato Grosso, and, through the clustering technique, to analyze the formation of groups to propose a zoning microclimate in the area study. To this end, collection data of air temperature and relative humidity at 15 points in two seasons (April to September) at three times (8h, 14h and 20h) was held in 2010. The results showed that sites with a predominance of buildings with asphalt pavement had high temperatures and low humidity, revealing the importance of introducing trees. The cluster analysis showed that the combination of data of air temperature and relative humidity provides a better grouping of the points with a smaller distance connection to the formation of groups. It is noted that the use of the clustering technique was satisfactory for the microclimatic zoning at the Cuiabá campus of Universidade Federal de Mato Grosso, which can be used in microclimatic scale.